2020
DOI: 10.1016/j.psychres.2020.113392
|View full text |Cite
|
Sign up to set email alerts
|

Three months of loneliness during the COVID-19 lockdown

Abstract: The majority of the U.S. population has been under stay-at-home restrictions to reduce the spread of COVID-19 since March 2020. Over the first three months of restrictions, 3,121 U.S. adults completed the UCLA Loneliness Scale-3 and Patient Health Questionnaire-9 (PHQ-9). Despite relaxation of lockdowns and shelter-in-place orders over that time, loneliness scores increased significantly, particularly from April to May 2020, and appear to have plateaued by June. Loneliness was correlated with depression and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
129
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(153 citation statements)
references
References 5 publications
11
129
2
1
Order By: Relevance
“…These results seem to differ strongly from the studies by McGinty et al [ 22 ] and Daly et al [ 9 ], and especially Twenge and Joiner [ 7 ], but we cannot rule out the possibility that differences in study designs, among other things, play a role in these differences. For instance, these studies compared different pre- and post-COVID outbreak study samples instead of pre- and post-COVID-19 outbreak assessments within the same sample.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…These results seem to differ strongly from the studies by McGinty et al [ 22 ] and Daly et al [ 9 ], and especially Twenge and Joiner [ 7 ], but we cannot rule out the possibility that differences in study designs, among other things, play a role in these differences. For instance, these studies compared different pre- and post-COVID outbreak study samples instead of pre- and post-COVID-19 outbreak assessments within the same sample.…”
Section: Discussioncontrasting
confidence: 98%
“…Bu et al [ 21 ] compared loneliness data of the large UK Household Longitudinal Study (wave 9; January 2017- June 2019) with loneliness data of the COVID-19 Social Study (March-May 2020), and found that loneliness levels were higher in the COVID-19 Social Study. In the longitudinal study by Killgore et al [ 22 ], using the US Mechanical Turk (MTurk) crowdsourcing platform, loneliness increased significantly from March to June 2020, particularly from April to May 2020. Only one longitudinal study among the adult general population was identified using pre-outbreak data on loneliness of the study sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are also congruent with recent studies suggesting that loneliness is the main risk factor for depression, anxiety, and their comorbidity (Palgi et al, 2020), and loneliness may explain a significant portion of the variance of psychiatric symptoms observed in individuals during the COVID-19 crisis (Tso and Park, 2020). Furthermore, similarly to our findings, Killgore et al (2020b) observed significant correlation between loneliness and both depression and suicidal ideation at all three data points of the study. Surprisingly, we observed the cross-lagged influence of initial COVID-19 response on subsequent levels of loneliness in social distancing individuals.…”
Section: Discussionsupporting
confidence: 93%
“…These include reduced levels of physical activity [ 1 , 2 ], poorer diet [ 3 ], and an increased prevalence of sleep problems [ 4 ]. Various psychosocial consequences of lockdown have also been reported, including higher rates of loneliness [ 5 , 6 ], less social cohesion (particularly in deprived communities) [ 7 ], more mental health difficulties, and a decrease in psychological wellbeing [ 8 , 9 , 10 ]. Potentially positive consequences of lockdown have also been described; for instance, studies of adults in Egypt, India, and the US report a moderate increase in perceived social support during lockdown [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%